Seasonal Changes of Microbial Load in Some Sea Foods from Buguma and Ekerekana Creeks, Niger Delta, Nigeria - Olajunmoke Modupe Edun; Ojo Andrew Akinrotimi; Oluwaseun Opeyemi Makinde (Annals of Environmental Science and Toxicology - Peertechz Publications, 2016)
Background and Aim: Niger delta environment has been exposed to organic and inorganic contaminants from industries and domestic wastes, thereby enhancing the capacity of the ecosystem into harboring a sizeable population of microorganisms. Most of these microorganisms are found in the water column, bottom sediment and water film, resulting in their elevated levels in seafood. Proper understanding of the transfer of microorganisms through the food web is essential to predict the exposure of seafood consumers to possible health consequences associated with its consumption in the coastal areas. Hence, the present study examines the microbial content of some sea foods such as: periwinkle (Tympanotonus fuscatus); mudskipper (Periophthalmus papilio); mullets (Liza falcipinis) Oyster (Crassotrea gasar) and water from Ekerekana and Buguma creeks, in the Niger delta, Nigeria. Methods: Seasonal variations in microbial content in some seafood namely: Periwinkle (T. fuscatus); mudskipper (P. papilio); mullet (L. falcipinnis) and Oyster (C. gasar) from Ekerekana and Buguma creeks, Niger delta, Nigeria were assessed. The sea foods were sampled monthly from both creeks for a period of eight months. Standard methods were employed in the evaluation of microbial load in each species. Results: The result indicated that the microorganisms isolated: total heterotrophic bacteria count, total vibro count; and total coliform count were more predominant in the wet season when compared to dry season months. Total coliform count bacteria exhibited some measure of elevation in the dry season months, an indication that they can be prevalent in both seasons depending on the type of human activities that is prevalent in the area. Conclusion: This study has shown that industrial and domestic wastes discharged into Ekerekana and Buguma creek resulted in high concentrations of pollutants in the water body, which promotes the growth of microorganisms in the water column and sea foods, this may pose a health hazard to humans as a final consumer of these organisms There is therefore the need to formulate appropriate policies and regulations for safeguarding the ecosystem from adding undesirable microbial population.